2023
DOI: 10.18280/jesa.560314
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid RPI-MCDM Approach for FMEA: A Case Study on Belt Conveyor in Bir El Ater Mine, Algeria

Radhouane Moghrani,
Zoubir Aoulmi,
Moussa Attia

Abstract: Failure Modes and Effects Analysis (FMEA) is a widely-used technique for enhancing dependability by ranking failure modes according to their Risk Priority Number (RPN). However, RPN has limitations, such as non-injectivity, non-surjectivity, and difficulties in weighing risk variables. The Risk Prioritization Index (RPI) model offers an alternative, addressing some of these limitations and providing user-friendly prioritization of failure modes. This study proposes an integrated risk assessment model that comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In comparing our study's findings with existing literature, it's evident that our results corroborate the effectiveness of MCDM methods in optimizing drilling processes It is in line with the studies conducted in the studies [24] and [26]. Specifically, our use of TOPSIS and VIKOR methods for evaluating drilling efficiency mirrors the approach by the study [27], who also applied MCDM techniques in a mining context. However, the stronger correlation and agreement observed between TOPSIS rankings and the reference rankings in our study contrast with the moderate alignment reported in the research [28] on failure mode analysis.…”
Section: Figure 3 Alternative Ranking Obtained Using Different Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In comparing our study's findings with existing literature, it's evident that our results corroborate the effectiveness of MCDM methods in optimizing drilling processes It is in line with the studies conducted in the studies [24] and [26]. Specifically, our use of TOPSIS and VIKOR methods for evaluating drilling efficiency mirrors the approach by the study [27], who also applied MCDM techniques in a mining context. However, the stronger correlation and agreement observed between TOPSIS rankings and the reference rankings in our study contrast with the moderate alignment reported in the research [28] on failure mode analysis.…”
Section: Figure 3 Alternative Ranking Obtained Using Different Methodssupporting
confidence: 87%
“…It is a systematic and structured technique that helps decision-makers make informed choices. Here's TOPSIS Steps [27], To further clarify the TOPSIS methodology, it is based on the principle that the chosen alternative should have the shortest Euclidean distance from the Positive Ideal Solution (PIS) and the furthest Euclidean distance from the Negative Ideal Solution (NIS). This presupposes a perfectly compensatory decision-making model in which high scores on some criteria can offset low scores on others.…”
Section: Topsis Approachmentioning
confidence: 99%
“…Additionally, Özfırat et al (2022) have done Event Tree Analysis (ETA) for each previously identified risk to display and decrease their severity degrees. A study by Moghrani et al (2023) took a step further, proposing a RPI-MCDM-based FMEA evaluation model that classifies failure modes of systems and machines in order to enhance failure modes in belt conveyor systems and the mining industry in general. Although numerous authors analyzed risk inside a mining environment, most of the research was done from a safety perspective, where potential hazards were perceived as the main consequence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At loading and unloading locations, there are occasionally wait durations. The waiting periods at these stations raise the unit cost per material carried since they lower operating capacity [9]. It is clear that when there is over-or undertrucking, waiting times happen.…”
Section: Introductionmentioning
confidence: 99%